POETRY AS A TOOL FOR DEVELOPING CREATIVE WRITING SKILLS IN ESL AND EFI CONTEXTS - Nirumala Rothinam (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The use of poetry as a pedagogical tool in English as a Second Language and English as a Foreign Language context has gained increasing attention for its potential to support creative writing development. However, existing empirical research remains fragmented across instructional approaches, learner populations, and outcome measures. This systematic literature review synthesises research published between 2010 and 2025 on the role of poetry in developing creative writing skills among ESL and EFL learners. Guided by the PRISMA framework, peer reviewed journal articles were identified through Scopus and Web of Science databases using predefined inclusion and exclusion criteria. A total of eligible studies was subjected to qualitative synthesis and bibliometric analysis. VOSviewer was employed to conduct keyword co-occurrence analysis, thematic mapping, and research cluster visualisation to identify dominant research trends, conceptual linkages, and under explored areas. Findings indicate that poetry-based instruction supports multiple dimensions of creative writing, including imagery, metaphorical thinking, voice, emotional expression, and linguistic experimentation. Poetry is frequently positioned as a low anxiety medium that enhances learner engagement, motivation, and confidence in written expression, particularly in ESL and EFL classrooms where linguistic constraints often inhibit creativity. Bibliometric mapping reveals three dominant research clusters, namely poetry and language creativity, affective engagement and identity expression, and instructional strategies for creative writing development. Despite positive outcomes, gaps remain in longitudinal research, assessment practices, and comparative studies across proficiency levels and educational settings. This review contributes a structured synthesis of the pedagogical and theoretical foundations of poetry based creative writing instruction in ESL and EFL contexts. It also provides a bibliometric overview to inform future empirical research, curriculum design, and teacher professional development in creative writing pedagogy.